2022
DOI: 10.1002/anie.202115593
|View full text |Cite
|
Sign up to set email alerts
|

Radical 1‐Fluorosulfonyl‐2‐alkynylation of Unactivated Alkenes

Abstract: Sulfonyl fluorides have found widespread use in chemical biology and drug discovery. The development of synthetic methods for the introduction of the sulfonyl fluoride moiety is therefore of importance. Herein, a transition-metalfree radical 1,2-difunctionalization of unactivated alkenes via FSO 2 -radical addition with subsequent vicinal alkynylation to access β-alkynyl-fluorosulfonylalkanes is presented. Alkynyl sulfonyl fluorides are introduced as highly valuable bifunctional radical trapping reagents that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 91 publications
0
36
0
Order By: Relevance
“…β-Keto sulfonyl fluorides have drawn special attention as they are highly functionalized with both fluorosulfonyl motifs and carbonyl groups, enabled with further possibility of post-functionalizations. Yet, compared to the well-developed methods to synthesize aliphatic 5 or aromatic 6 sulfonyl fluorides, strategies to prepare β-keto sulfonyl fluorides remain less explored. Early in 1990, Seppelt and co-workers reported a useful synthesis of β-keto sulfonyl fluoride through a multiple-step procedure with ketene (g) and SF 5 Cl (g) (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…β-Keto sulfonyl fluorides have drawn special attention as they are highly functionalized with both fluorosulfonyl motifs and carbonyl groups, enabled with further possibility of post-functionalizations. Yet, compared to the well-developed methods to synthesize aliphatic 5 or aromatic 6 sulfonyl fluorides, strategies to prepare β-keto sulfonyl fluorides remain less explored. Early in 1990, Seppelt and co-workers reported a useful synthesis of β-keto sulfonyl fluoride through a multiple-step procedure with ketene (g) and SF 5 Cl (g) (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…8 Typical methods mainly include: (1) accessing the fluorosulfonyl group via the chloride–fluoride exchange 9 and alternative methods; 10 (2) introducing sulfonyl fluoride fragments into the target molecules via sulfonyl fluoride hubs; 11 and (3) direct fluorosulfonylation via FSO 2 reagents or FSO 2 synthons. 12 Due to decades of development, the classic approaches to access the fluorosulfonyl group have proven to be a straightforward and efficient way.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonyl fluorides have been receiving dramatically increasing attention, since Sharpless introduced sulfur­(VI) fluoride exchange (SuFEx) as the next click reaction in 2014 . Indeed, they are important compounds, finding various applications in chemical biology, drug discovery, organic synthesis, polymer science, etc. Accordingly, new synthetic methods have been rapidly developed to access these motifs, particularly multifunctional sulfonyl fluorides including sulfonyl fluoride-substituted aryl halides, , sulfonyl fluoride-substituted boronic acids, ethenesulfonyl fluoride (ESF) and its derivatives, , 2-substituted-alkynyl-1-sulfonyl fluorides (SASF), β-chloro alkenylsulfonyl fluorides (BCASF), and β-alkynyl-fluorosulfonyl alkanes (BAFSA) …”
mentioning
confidence: 99%
“…1−10 Accordingly, new synthetic methods have been rapidly developed to access these motifs, 11−19 particularly multifunctional sulfonyl fluorides including sulfonyl fluoride-substituted aryl halides, 20,21 sulfonyl fluoride-substituted boronic acids, 22 ethenesulfonyl fluoride (ESF) and its derivatives, 23, 24 2-substituted-alkynyl-1-sulfonyl fluorides (SASF), 25 β-chloro alkenylsulfonyl fluorides (BCASF), 26 and β-alkynyl-fluorosulfonyl alkanes (BAFSA). 27 Recently, we have demonstrated that β-keto sulfonyl fluorides (BKSF), 28 as a new class of multifunctional sulfonyl fluorides, can serve as connective SuFEx hubs for creating a variety of functional molecules (Scheme 1A). In addition, these molecules are important bioactive motifs, showing promise as control agents against plant diseases.…”
mentioning
confidence: 99%